2014
DOI: 10.1016/j.aop.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

General monogamy property of global quantum discord and the application

Abstract: We provide a family of general monogamy inequalities for global quantum discord (GQD), which can be considered as an extension of the usual discord monogamy inequality. It can be shown that those inequalities are satisfied under the similar condition for the holding of usual monogamy relation. We find that there is an intrinsic connection among them. Furthermore, we present a different type of monogamy inequality and prove that it holds under the condition that the bipartite GQDs do not increase when tracing o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 52 publications
(63 reference statements)
1
13
0
1
Order By: Relevance
“…In recent years, the relation between QPTs and quantum information has caused great attention, and several concepts borrowed from quantum information science are successfully used in the study on QPTs 6 7 8 9 10 11 12 13 14 15 ; these concepts include entanglement 8 9 , mutual information 10 , quantum fidelity 12 14 , and quantum discord (QD) 15 16 17 . Very recently, the relationship between QPTs and the ground-state local convertibility is investigated in ref.…”
mentioning
confidence: 99%
“…In recent years, the relation between QPTs and quantum information has caused great attention, and several concepts borrowed from quantum information science are successfully used in the study on QPTs 6 7 8 9 10 11 12 13 14 15 ; these concepts include entanglement 8 9 , mutual information 10 , quantum fidelity 12 14 , and quantum discord (QD) 15 16 17 . Very recently, the relationship between QPTs and the ground-state local convertibility is investigated in ref.…”
mentioning
confidence: 99%
“…Thus, all classical extensions of separable states are polygamous in the usual sense. This observation i) constitutes the basic argument in demonstrating that quantum correlations are not monogamous in general [25] and ii) underlies the violation of more general monogamy relations, even for multipartite correlation measures [29,30]. However, there exist monogamy relations valid even for classical extensions if we consider some generalized multipartite quantum correlations.…”
Section: Monogamy Of Correlationsmentioning
confidence: 99%
“…It is well known that classical correlations are infinitely shareable whereas there is a restriction on the shareability of quantum entanglement amongst the several parts of a multipartite quantum state [1][2][3][4]. The concept of monogamy of entanglement and monogamy of quantum correlations has been studied quite extensively [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and it is shown that the measures of quantum correlations such as quantum discord [19], quantum deficit [20] are not monogamous for some category of pure states [11,12]. The polygamous nature of quantum correlations other than entanglement has initiated discussions on the properties to be satisfied by a correlation measure to be monogamous [16] and it is shown that a measure of correlations is in general non-monogamous if it does not vanish on the set of all separable states [16].…”
Section: Introductionmentioning
confidence: 99%